Pengembangan Produk Panna Cotta Bir Pletok Berbahan Dasar Jahe Merah (Zingiber Officinale Var. Rubrum), Serai (Cymbopogon Citratus) Dan Kayu Secang (Caesalpinia Sappan) - Nurhidayati, Vieta Annisa; Rizkiriani, Annisa; Nuraeni, Ani; Riski, Astari; An Najihah, Syahidah Endrini; Munawarah, Siti (Jurnal Gizi dan Kuliner, 2022)
Pletok beer is a traditional Indonesian drink made from ginger, lemongrass, sappan wood and other spices with high antioxidant content. Pletok beer is currently less popular to young consumers. The modification of the Pletok beer product in the form of panna cotta is expected to increase the value of Pletok beer among consumers. This study aimed to find Pletok Beer Panna Cotta formulation preferred by the consumers. The study used a completely randomized design with three treatments. Formula 1, 2, and 3 are panna cotta products with main additives, namely whipping cream, plain milk, and heavy cream, respectively. Hedonic test was performed to 30 untrained panelists using a 5-scale Likert questionnaire with indicators assessing appearance, color, taste, aroma, and texture. The test results showed that formula with added ingredients of plain milk have better preference scores in color and appearance, while formulas with added ingredients of heavy cream have better preference scores in taste and texture. Overall, the formulation of Beer Pletok Panna Cotta favored by the panelists were products with heavy cream added or Formula 3.